PSI-15 Feeding garlic powder at low doses does not negatively affect feedlot cattle health. (30th November 2020) - Cheang-Deis, Iris; Lardner, Bart; Rochon, Kateryn; Barkema, Herman W; Block, Hushton; Cook, Nigel; Durunna, Obioha N
Abstract: Antimicrobial and insectifugal effects have been reported for dehydrated garlic powder. With limited knowledge of its impact on the health of beef cattle, this study investigated whether free-choice minerals infused with garlic powder affected cattle blood parameters and long-term stress during the summer. A total of 104 crossbred steers (26 steers per group) were randomly assigned to either 0% garlic product (Control), 0.3% garlic-oil-based premix (GOil), 2.5% garlic powder (2.5% GP) or 5% garlic powder (5% GP). Feed and mineral supplements were fed separately in individual GrowSafe® bunks to monitor each steer's feed and mineral intake. Measures of individual steer performance collected include body weights and gains, feed intake and ultrasound body fat levels. Blood was collected from 10 steers with the greatest intake and 5 steers with the least mineral intake in each group for biochemical and hematological analyses. Hair samples were clipped from each steer (3 times) from the rump region to evaluate differences cortisol levels as a measure of long-term stress. Preliminary results showed no difference in final body weight (P =0.19) and dry matter intake (P =0.89). However, compared with the control, all garlic treatment groups had greater average daily mineral intake (P = 0.003). The group that received GOil had a greater average daily gain (P = 0.002) and more gain-to-feed ratio (P =0.01) than other groups. No difference (P >0.05) was observed in most serum biochemical parameters with the exception of 5% GP that had a significantly lower bilirubin (P = 0.0001) and albumin (P = 0.002) concentration but all biochemical and hematological measurements fell within the normal range for beef cattle. There was no difference (P = 0.29) among the groups for cortisol levels. The preliminary results show that low-dose infusion of garlic powder was not associated with any adverse health conditions in beef cattle.